2001
DOI: 10.4141/p00-133
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among bread-making quality, gluten strength, physical dough properties, and pasta cooking quality for some Canadian durum wheat genotypes

Abstract: . 2001. Relationships among bread-making quality, gluten strength, physical dough properties, and pasta cooking quality for some Canadian durum wheat genotypes. Can. J. Plant Sci. 81: 611-620. Fifty-four durum wheat (Triticum durum) genotypes entered into the 1995, 1996 and 1997 Co-operative Tests were evaluated for gluten strength characteristics using the sodium dodecyl sulphate (SDS) sedimentation test, the gluten index (GI) test, and physical dough tests including farinograph (high and low adsorption), mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…These results were in agreement with Marchylo et al (2001), that obtained significant correlations between bread volume and alveograph deformation energy and farinograph development time in a study with 54 durum wheat. Bread weight was significantly correlated with volume (p<0.001) and alveograph parameters (p<0.01 with W and p<0.05 with P/L), but it was not correlated with farinograph parameters, except water absorption (p<0.05).…”
Section: Relation Between Quality Traitssupporting
confidence: 82%
See 1 more Smart Citation
“…These results were in agreement with Marchylo et al (2001), that obtained significant correlations between bread volume and alveograph deformation energy and farinograph development time in a study with 54 durum wheat. Bread weight was significantly correlated with volume (p<0.001) and alveograph parameters (p<0.01 with W and p<0.05 with P/L), but it was not correlated with farinograph parameters, except water absorption (p<0.05).…”
Section: Relation Between Quality Traitssupporting
confidence: 82%
“…The farinograph parameters were significantly related to each other and with the alveograph deformation energy as expected (Marchylo et al, 2001). P/L ratio only was significantly correlated with farinograph stability (p<0.001).…”
Section: Relation Between Quality Traitsmentioning
confidence: 60%
“…Cubbada et al (1992) calculated a correlation coefficient of -0.25 with the dry gluten content. The GI was correlated moderately with the wet gluten content (-0.41, Peña 2000) and weakly (-0.32 to -0.25, Clarke et al 2010) or not significantly (Marchylo et al 2001) with the protein content. Longin et al (2013) reported correlation coefficients of 0.38 and 0.45 between the GI and wet gluten content in two sets of winter durum wheat genotypes.…”
Section: Effect Of Meteorological Factors On Gimentioning
confidence: 92%
“…Cooking quality was affected to a similar extent by genotype and environment. 6,7 In Sardinia, as in most regions with a Mediterranean climate, crops face a wide range of growing conditions which induce wide variability in yield and quality. Durum wheat is the dominant cereal crop in the Mediterranean crop growing region due to its resistance to drought and high temperature, particularly in late spring, when the grains are ripening.…”
Section: Introductionmentioning
confidence: 99%